Analysis of Selected Cardiovascular Biomarkers in Takotsubo Cardiomyopathy and the Most Frequent Cardiomyopathies - Topf, Albert; Mirna, Moritz; Bacher, Nina; Paar, Vera; Motloch, Lukas J.; Ohnewein, Bernhard; Larbig, Robert; Grueninger, Janine; Hoppe, Uta C.; Lichtenauer, Michael; Pistulli, Rudin (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Among the causes of de novo diagnosed cardiomyopathy, Takotsubo cardiomyopathy (TTC) plays a minor role, with an occurrence of 50,000–100,000 cases per annum in the United States. In clinical practice, a differentiation of a TTC toward an ischemic cardiomyopathy (ICMP) or a dilatative cardiomyopathy (DCMP) appears to be challenging, especially in a subacute setting or in atypical types of TTC. Methods: To investigate this issue, we analyzed serum levels of sST2, GDF-15, suPAR, HFABP, and clinical parameters including echocardiography in 51 patients with TTC, 52 patients with ischemic cardiomyopathy (ICMP) and 65 patients with dilated cardiomyopathy (DCMP). Results: sST-2 seemed to be the most promising biomarker for prediction of a TTC in differential diagnosis to an ICMP (AUC: 0.879, p = < 0.001, Cut off values: 12,140.5 pg/ml) or to a DCMP (AUC: 0.881, p = < 0.001, cut off value: 14521.9 pg/ml). GDF-15 evidenced a slightly lower AUC for prediction of a TTC in differential diagnosis to an ICMP (AUC: 0.626, p = 0.028) and to a DCMP (AUC: 0.653, p = 0.007). A differential diagnostic value was found for H-FABP in the prediction of a DCMP compared to TTC patients (AUC: 0.686, p = < 0.001). In propensity score matching for left ventricular ejection fraction, sex, and cardiovascular risk factors, differences in the plasma levels of sST2 and H-FABP in the matched cohort of TTC vs. DCMP remained statistically significant. In the matched cohort of TTC vs. ICMP, differences in sST2 also remained statistically significant Conclusion: As medical therapy, long term prognosis, interval of follow-ups, rehabilitation program and recommendations differ completely between TTC and ICMP/DCMP, biomarkers for differential diagnosis, or rather for confirmation of diagnosis, are warranted in cases of cardiomyopathies with unsure origin. sST-2, GDF-15 and H-FABP might facilitate the classification.